Efficient dye degradation and THz spectra of PMo12 based rare earth phosphine oxide complexes. Issue 40 (5th October 2022) - Hu, Cong; Li, Ying-Yu; Qiu, Qi-Ming; Han, Hong-Liang; Gu, Chao-Yue; Yang, Yu-Ping; Dai, Li-Xiong; Jin, Qiong-Hua
Abstract : PMo12 based rare earth phosphine oxide complexes have good adsorption properties for rhodamine B and can degrade methylene blue under UV irradiation. Abstract : In today's world, water pollution is a serious problem. Dye adsorption and photocatalytic degradation are effective methods to deal with water pollution. The key to dealing with water pollution is to find suitable adsorbents and catalysts. We synthesized a series of rare earth complexes containing [PMo12 O40 ] 3− and a PO ligand, [REL4 ](PMo12 O40 )· n CH3 CN (RE = La for 1, Ce for 2, Pr for 3, Sm for 4, Eu for 5, Gd for 6, and Tb for 7 ; n 1, 2, 3, 5, 6 = 2 and n 4, 7 = 0; L = tetraethyl ethylenediphosphonate), and [REL3 (H2 O)](PMo12 O40 )·CH3 CN (RE = Tm for 8, Yb for 9, and Y for 10 ). Complexes 1–7 are all eight-coordinated mononuclear structures centered on lanthanide ions, [PMo12 O40 ] 3− anions and solvent molecules are not coordinated with metal ions, while complexes 8–10 are seven-coordinated mononuclear structures. These mononuclear structures eventually form complicated 3D supramolecular structures through hydrogen bond weak interactions. These complexes have good adsorption properties for rhodamine B (RhB) and can degrade methylene blue (MB) under UV irradiation. Furthermore, terahertz time-domain spectroscopy (THz-TDS) is used to characterize the structures of complexes and ligands, which will provide useful information for building bridges between THz spectra and the structures of complexes in coordination chemistry.